Load-settlement response of strip footing on layered soils with inclined interface under general load combinations - Xiong, Neng (2017)
This final year project aims to study the load-settlement response of a strip footing on layered soil with inclined interface and general load combinations. Past studies on elastic settlement and bearing capacity of a strip footing on layered or inclined soils are reviewed. Finite Element Method (FEM) is briefly introduced and a detailed scope of work is presented based on Plaxis 2D FEM software. The average and differential elastic settlement under vertical loading subjected to varying interface inclination, depth of soil interface, and soil stiffness are firstly investigated. The bearing capacity subjected to combined loadings with interface inclination and depth of soil interface is then investigated. It is observed that the interface inclination has no significant impact on average elastic settlement, and appears to have greater effect on differential settlement and bearing capacity. Moreover, the depth of soil interface appears to influence average and differential settlement significantly and reduce the effect of interface inclination on bearing capacity. Finally, combined loadings can lead to different failure envelope or failure surfaces given different loading patterns. Recommendations on future work and a brief summary are presented at the end of the project report.